LITERASI EKONOMI SYARIAH PADA SANTRI PONDOK PESANTREN BAHRUL ULUM TAMBAKBERAS KABUPATEN JOMBANG - Rahmawati, Zeni; indrarini, rachma (Jurnal Ekonomika dan Bisnis Islam, 2021)
Islamic economics and finance in Indonesia have developed rapidly in last two decades. However, Indonesia’s Islamic economic literacy is still low at 16,3%. One way that the government has taken toincrease Islamic economic literacy is by encouraging Islamic boarding schools to increase Islamic economic and financial literacy.  The purpose of this research is to determine the level of Islamic economic literacy High School Santri of Islamic Boarding School Bahrul Ulum Tambakberas Jombang using a quantitative approach. Sources of data in this research are primary data and secondary data. Primary data is obtained from answers given by respondents in distributed questionnaires. Secondary data were obtained from library research. The number of respondents was 89 santri. Data were collected using a questionnaire. The test on the research instrument was the validity test and reliability test. The data analysis technique used is descriptive statistics. The result showed that the Islamic economic literacy level of santri was in the sufficient literate category with an average of 73,64%. The Islamic economic literacy index is obtained by calculating the literacy rate of each aspect multiplied by the weight of the constituent aspects, so the result of islamic economic literacy index of santri is 36,61% (well literate).